Mucinous carcinoma of breast with neuroendocrine differentiation: a rare case report with review of literature - Anuradha, D.; Lakshmi, A. Bhagya (International Journal of Research in Medical Sciences, 2017)
Mucinous carcinoma of the breast is a relatively rare malignancy accounting for 2% of all breast cancers. Mucinous carcinoma of the breast has a favourable prognosis and is usually seen in postmenopausal women. Here, we report a 60 year old female patient presented with right breast lump was diagnosed on cytology as ductal carcinoma of the breast, on histopathology diagnosed as mucinous carcinoma with neuroendocrine differentiation, which was subsequently confirmed on IHC marker synaptophysin and chromogranin A positive.